English for Communication: Strengthening English Language Skills for Students at Pesantren Mahasiswa Darushohabah Jakarta - Gufron, Gufron (Universitas Persada Indonesia YAI, 2025)
This community service initiative (PkM) addressed the critical need for English communication skills among students at Pesantren Mahasiswa Darushohabah in Jakarta. Recognizing English proficiency as an essential global competency, the program targeted persistent challenges in oral communication faced by pesantren students (Santri) due to limited practice opportunities and confidence issues. The